Evaluation of Chloride-Induced Corrosion of Reinforced Steel Bars in Concrete Using Half-Cell Potential Method: Factor of Sodium Chloride Solution Amount and Acceleration Period - Phoo-ngernkham, Tanakorn; Plongkrathok, Chittinat; Phiangphimai, Chattarika; Chompoovong, Khattiya; Detphan, Chudapak; Detphan, Satakhun; Hanjitsuwan, Sakonwan (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This paper aims to evaluate the chloride-induced corrosion of reinforced steel bars in concrete using the half-cell potential (HCP) method. The corrosion of reinforced steel bars in concrete was examined in connection with the amount of sodium chloride (NaCl) solution and the acceleration period. The differences in NaCl solution amounts of 25 %, 50 %, and 75 % by the height of the concrete sample, acceleration periods of 3, 6, and 9 hours, and concrete covering depths were investigated in this study. Test results found that the corrosion probability of reinforced concrete tended to increase with increasing NaCl solution proportion and acceleration period. Furthermore, an increase in the depth of concrete covering could reduce the corrosion of reinforced steel bars in concrete. According to test results, it is recommended that the NaCl solution amount at 25 % of the height of the concrete sample and the acceleration period at 3 hours are suitable conditions for testing in the laboratory regarding cost-effectiveness and testing period. The average HCP readings of reinforced concrete samples were below -400 mV/CSE at the time of measurement.